The carotid web: Current research status and imaging features - Liang, Shixiao; Qin, Peixin; Xie, Lili; Niu, Shanshan; Luo, Junqi; Chen, Fei; Chen, Xiangmeng; Zhang, Jie; Wang, Guojie (Frontiers in Neuroscience, 2023)
The carotid web is commonly found in the carotid bulb or beginning of the internal carotid artery. It presents as a thin layer of proliferative intimal tissue originating from the arterial wall and extending into the vessel lumen. A large body of research has proven that the carotid web is a risk factor for ischemic stroke. This review summarizes the current research status of the carotid web and focuses on its imaging presentation.